POLA KERJA SAMA ANTARA ORANG TUA DAN GURU DALAM PEMBELAJARAN BACAAN SHALAT DI RA AL-AMIN - Nabila Nabila; Dedi Masri; Raya Idul Fitri; Raihan Nazrey Suseno (incrementapedia, 2022)
This study describes several external policies of RA Al-Amin in order to improve the quality of education at RA Al-Amin. The type of research in this paper is descriptive qualitative. Data collection techniques used by way of interviews and also various sources both from relevant books and journals. The results of this study indicate that the external policies set by RA Al-Amin consist of: (1) Prayer reading assistance, intending to educate the character of students to obey and obey Allah SWT through prayer, (2) Application of cooperation between parents and teachers in learning prayer readings for children, the application of this policy is expected to make it easier for children to memorize prayer readings, (3) Implementation of practice, getting children to pray correctly which is done together. (4) Repetition, parents have the duty to repeat the lessons that their children have learned at school. As for the inhibiting factors of this policy are external factors where both parents are busy working, as well as the community environment.